2018
DOI: 10.4300/jgme-d-16-00716.1
|View full text |Cite
|
Sign up to set email alerts
|

A Descriptive Analysis of the Use of Twitter by Emergency Medicine Residency Programs

Abstract: Applications and usage among EM residency programs are varied, and are frequently not consistent with current CORD recommendations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 14 publications
(15 reference statements)
1
16
0
Order By: Relevance
“…Medical Education. This theme shows the research on using Twitter for medical education purposes such as online discussion on program evaluation [109] and research papers [110], professional development [111], and utilizing Twitter in emergency medicine residency programs [112] and medical conferences [113]. Having a significant change, the medical education theme have a decreasing trend.…”
Section: The Second Category Represented Common Research Paperrelatedmentioning
confidence: 99%
“…Medical Education. This theme shows the research on using Twitter for medical education purposes such as online discussion on program evaluation [109] and research papers [110], professional development [111], and utilizing Twitter in emergency medicine residency programs [112] and medical conferences [113]. Having a significant change, the medical education theme have a decreasing trend.…”
Section: The Second Category Represented Common Research Paperrelatedmentioning
confidence: 99%
“…Pharmacy educators have incorporated social media into teaching and precepting strategies to increase exposure to novel ideas and practices, and to educate learners on the utility of Twitter as a professional resource 3‐5 . While the presence of the medical community on Twitter, including medical residencies, 6 has seen continuous growth in recent years, pharmacy residency programs have only just begun to realize the merits of this platform. Instagram and Facebook are additional social media platforms with the capability to highlight program activity; however, they are generally less established from a pharmacy community standpoint.…”
Section: Figurementioning
confidence: 99%
“…Theoretically, Twitter provides residency programs the ability to disseminate knowledge in novel ways and to draw attention to its residents' accomplishments. Literature on the impact of social media use by residency programs is expanding, though only draws from a few different types of residency programs (St Claire et al, 2019;Xie et al, 2018;Diller and Yarris, 2018;Lamb et al, 2017;Hass et al, 2016). Focus tends to be placed on educational content, though one study from an internal medicine program twitter account analysis found that the small number of tweets highlighting resident accomplishments or social events (N=49) were rated as highly informative by the majority of residents (80%) (Bergl, Narang and Arora, 2015).…”
Section: Introductionmentioning
confidence: 99%